PERAN KELUARGA TERHADAP PENCEGAHAN KEKERASAN SEKSUAL BERBASIS ELEKTRONIK PERSPEKTIF HUKUM PERKAWINAN ISLAM - Deza Musfirah; Fatroyah Ars Himsyah; Jamiliya Susantin (Program Studi Hukum Keluarga Islam, 2023)
Electronic Based Sexual Violence (KSBE) is a new type of violence. Many children are victims of this type of violence. Parents have an important role in prevention. The aims of this research are: (1) To explain the role of prevention that can be carried out by the family against electronic-based sexual violence according to the perspective of Islamic marriage law: (2) To know the legal consequences for parents who are negligent in preventing Electronic-Based Sexual Violence. This type of research is library research, with primary legal materials in the form of Komnas Perempuan's annual notebooks, Islamic marriage law books, Al-Quran, Hadith, and Laws, as well as secondary legal materials, namely scientific journals, articles that intersect with the legal topics studied. and tertiary legal materials in the form of an Indonesian dictionary. Legal materials are collected by reviewing, recording, and evaluating library materials, as well as searching through the internet and analyzing legal materials by interpreting the legal materials that have been processed. The results of the study show that: (1) the role of prevention that can be carried out by the family against KSBE from the perspective of Islamic marriage law, namely: providing education to children, supervising children, and giving love and affection to children. (2) As a legal consequence of parents' negligence in preventing the occurrence of KSBE in children, the parents' authority can be revoked for a certain time at the request of other parents with a court decision. Keywords: Electronic Based Sexual Violence, Family Role, Islamic Marriage Law